Maximizing Customer Loyalty Through Instagram-Based Engagement Strategies: A Content Analysis Of The Beauty Industry (International Journal of Environmental Sciences, 2025)
The beauty industry is increasingly leveraging digital platforms, particularly Instagram, to encourage customer engagement and enhance brand experiences. With the growing emphasis on content-driven marketing, Instagram has emerged as a key channel for customer engagement, brand advocacy, and customer loyalty. To explore the strategic content of Instagram organic posts in enhancing customer loyalty through effective engagement within the beauty industry. To investigate the effects of different content types of Instagram on customer engagement, such as customer loyalty based on the Uses and Gratification Theory (UGT). This conceptual paper utilizes a data-driven approach to analyze articles retrieved from databases (PubMed, Scopus, and Web of Science), covering the period from 2014 to 2025. Thematic analysis showed that emotional and cognitive content gratification, such as UGC, tutorials, and influencers' collaborations, show higher engagement (likes, shares, comments, and saves). Emotional, interactive, and personalized content significantly enhances customer engagement and customer loyalty in the beauty industry. Emotional content, such as storytelling, emerged as the strongest customer loyalty.